A Rotational BODIPY Nucleotide: An Environment-Sensitive Fluorescence-Lifetime Probe for DNA Interactions and Applications in Live-Cell Microscopy - Dziuba, Dmytro; Jurkiewicz, Piotr; Cebecauer, Marek; Hof, Martin; Hocek, Michal (Angewandte Chemie (International ed. in English), 2016)
Fluorescent probes for detecting the physical properties of cellular structures have become valuable tools in life sciences. The fluorescence lifetime of molecular rotors can be used to report on variations in local molecular packing or viscosity. We used a nucleoside linked to a meso-substituted BODIPY fluorescent molecular rotor (dC(bdp)) to sense changes in DNA microenvironment both in vitro and in living cells. DNA incorporating dC(bdp) can respond to interactions with DNA-binding proteins and lipids by changes in the fluorescence lifetimes in the range 0.5-2.2 ns. We can directly visualize changes in the local environment of exogenous DNA during transfection of living cells. Relatively long fluorescence lifetimes and extensive contrast for detecting changes in the microenvironment together with good photostability and versatility for DNA synthesis make this probe suitable for analysis of DNA-associated processes, cellular structures, and also DNA-based nanomaterials.
Keywords: Boron Compounds; nanostruktury; nukleotidy; Nanostructures; sloučeniny boru; HeLa buňky; rotace; konfokální mikroskopie; HeLa Cells; fluorescence; Rotation; Humans; Microscopy, Confocal; time-resolved spectroscopy; fluorescence spectroscopy; Fluorescent Dyes; Fluorescence; DNA; fluorescenční barviva; fluorescent probes; lidé; nucleosides; Nucleotides